LATERAL PERCUTANEOUS NEPHROLITHOTOMY: A CASE SERIES - Wijayanti, Zola; Vijay Pramod, Sawkar (Indonesian Urological Association, 2020)
Objective: To report our experience on lateral PCNL in the management of complex kidney stone in patients with many morbidities. Case(s) Presentation: In our hospital, there were 2 cases of incomplete stone clearance after PCNL which underwent lateral PCNL. The first case was a 47 years old woman who was morbidly obese and some cardiac problems such as coronary artery disease (CAD) and arrhythmia. Her intravenous pyelography shows that she has incomplete double collecting system with kidney stone in her upper moiety. She underwent PCNL in supine position which was halted due to arrhythmia with rest stone on her upper moiety system. The second case was a 57 years old male with multiple right kidney stone with hydronephrosis in his upper calyceal system. He has some comorbidities such as obese and CAD. He had history of open kidney surgery and right PCNL. Due to incomplete stone clearance after first procedure and some morbidities of those patients, we decided to perform PCNL on lateral position of both cases. The surgery went successfully with duration of 100 minutes in average with less than 100cc of blood loss. Both of the patients were discharged on second operation day without any complication. Discussion: Positioning for the patient who undergo PCNL is important. The lateral position of PCNL is useful in morbid obesity and have least effect on cardiac and respiratory function. This technique proved to increase patient comfort and safety. Conclusion: Lateral PCNL is safe and effective procedure to treat kidney stone in patients with history of incomplete stone clearance after supine or prone PCNL. It also can be performed safely in patients with comorbidities.